IMMERSION OF AR-VR INTO TOURISM INDUSTRY - Ankit Mondal , Pramod Damle (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
Virtual and Augmented Reality, in 21st century, is a technological gift that paves a new way for the researchers and Tourism Industry. In the COVID 19 era, where travellers will be extremely cautious in terms of future bookings as well as which destinations to select ? the closer they can be brought to the real experience the more inclined, they will be to make a decision, as well as an actual booking, for when lockdowns and social distancing restrictions have levelled out into a new normal and AR-VR turning out to be very crucial in the tourism and marketing scenario. The objective of this paper is to display the beneficiary aspects of indulging AR-VR into Tourism Arena to fight back the loss caused by COVID 19.